Reimaging Solidarity Feminist of Jesus in the Gospel of John 4:1-42 as Implications of Church Solidarity toward Women - ‎ , Darius (KnE Social Sciences, 2024)
One major concern of the freedom movement is the issue of feminism. Feminism movements exist to attack all acts of injustice toward women. Therefore, feminism is an effort or movement for women who demand emancipation, equality, and justice between the rights of men and women. This study describes the concept of Jesus’ feminist social solidarity in the Gospel of John 4:1–45 as a reflection of the church in applying feminist solidarity in various contexts. Therefore, the reflection of Jesus’ feminist solidarity is the basis for the church to maintain a balance between men and women, especially in service. The study utilizes the sociology hermeneutics and feminist hermeneutics approaches, both of which were carried out in an analytical descriptive manner. Sociological hermeneutics was used in the text of John 4:1–42 to analyze the sociological character of each of the characters in the text.1 Apart from that, feminist hermeneutics was applied to the text John 4:1–42 to reinterpret it in the light of the feminist movement to produce feminist solidarity centered on the feminist perspective of Jesus. The findings of the study show that: (1) Jesus’ outreach has destroyed the separator and lifted the degree of strata of Samaritan women’s society; (2) the kindness of Jesus is evidence of outreach to marginalized (women) groups; and (3) the feminist perspective of Jesus is empowering namely having become a Samaritan woman as a tool for Jesus to reach out. Keywords: solidarity, feminism, Gospel, Jesus, movement